The way to Pharmaceutical Care in Poland - practice, definitions and act - Iwona Arabas; Michał Byliniak; Katarzyna Maria Galon (Polish Pharmaceutical Society, 2021)
The role of pharmacists in patient care and pro-health education over the centuries. The way to Pharmaceutical Care in Poland and commentary to the new Pharmacist Profession Act. Purpose of research: Emphasizing the importance of Pharmaceutical Care in the light of the new Pharmacist Profession Act. Materials and methods: Source texts, scientific articles, specialist journals, legal acts. Results: The provision of medical advice and assistance to the sick by pharmacy staff is abundantly recorded in historical sources. At the beginning of the 19th century, commonly available medical guides were confronted with dangerous self-treatment. Attempts were made in places with difficult access to pharmacies and doctors to provide basic care through home (court) first-aid chest, the rules of which were contained in the 1844 Act "O apteczkach domowych i środkach podręcznych" ("On Household Medicine Cabinets and and First-Aid") and later repeated in 1920. There had been a debate over the decades, which in the 1990s led to the formation of an international movement for the "responsible provision of pharmacotherapy to achieve specific goals to improve patient quality of life". The information and educational obligations of pharmacists in the modern world began to play an increasingly important role, but they were never legally sanctioned although at the beginning of the 21st century, universities had already undertaken the task of introducing the subject of Pharmaceutical Care to the curriculum. An important step in bringing pharmacists closer to implementing pharmaceutical care was its inclusion in the government document "Polityka Lekowa Państwa 2018-2020 " ("State Drug Policy 2018-2020"). In 2020, the "Ustawa o zawodzie farmaceuty" (the Pharmacist Profession Act ") was passed. Its content indicates pharmaceutical care as one of the basic tasks of a pharmacist, also defining services that can be provided in pharmacies. Conclusions: The pharmacy has always been a natural place to provide help. The new Pharmacist Profession Act is proof of this and it enables the implementation of pharmaceutical care in pharmacies.